Differentiation

Calculus Level 1

If y = ( x 1 ) ( 2 x 2 + 3 ) y=(x-1)(2x^2+3) , find d y d x \dfrac {dy}{dx} .

6 x 3 + 4 x + 3 6x^3 +4x +3 6 x 2 4 x + 3 6x^2 - 4x +3 6 x 2 + 4 x 3 6x^2+ 4x -3 6 x 2 6 x + 3 6x^2-6x +3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Viki Zeta
Oct 13, 2016

d d x ( x 1 ) ( 2 x 2 + 3 ) = d d x u v ; u = ( x 1 ) , v = ( 2 x 2 + 3 ) = u v + v u = ( x 1 ) d d x ( 2 x 2 + 3 ) + ( 2 x 2 + 3 ) d d x ( x 1 ) = ( x 1 ) ( 4 x ) + ( 2 x 2 + 3 ) = 4 x 2 4 x + 2 x 2 + 3 = 6 x 2 4 x + 3 \dfrac{d}{dx} (x-1)(2x^2+3) = \dfrac{d}{dx} ~ uv; ~~ u = (x-1), \ v = (2x^2+3) \\ = uv' + vu' = (x-1)\dfrac{d}{dx}(2x^2+3) + (2x^2+3)\dfrac{d}{dx}(x-1) \\ = (x-1)(4x) + (2x^2+3) \\ = 4x^2 - 4x + 2x^2 + 3 \\ = 6x^2 - 4x + 3

@Vicky Vignesh Actually the question was to find dy/dt . Thats why I posted this problem. Initially I also thought that instead of dy/dt there should be dy/dx . But this problem is from chain rule p-set so probability of doing this problem by chain rule increases. (by substitution)

Saraswati Sharma - 4 years, 8 months ago

Log in to reply

Product rule is pretty easier than chain rule in this case.

Viki Zeta - 4 years, 8 months ago

Log in to reply

Conclusion - There should be dy/dx in p-sets rather than dy/dt which is creating a lot of confusion . There r straight 8 questions in my p-set with this same mistake .

Saraswati Sharma - 4 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...